2016
DOI: 10.1108/jmd-05-2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

Structural, linguistic and rhetorical features of the entrepreneurial pitch

Abstract: Purpose – As mastering the two-minute entrepreneurial pitch is a key skill required of entrepreneurs and all those who have to sell an idea in a business context, the purpose of this paper is to analyse successful entrepreneurial pitches in order to provide practical pitch-related advice to entrepreneurs and to business school instructors developing pedagogical materials. Design/methodology/approach – As mastering the two-minute entrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 18 publications
1
72
0
1
Order By: Relevance
“…Also, the review showed that some empirical research (see next section) were based on data collected from TV shows. Daly and Davy (2016a;2016b), for example, analyzed pitches from the Dragon's Den while Moreau (2018) explored pitches from its American counterpart, Shark Tank.…”
Section: Identifying Focuses Definitions and Purposes Of Pitchmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the review showed that some empirical research (see next section) were based on data collected from TV shows. Daly and Davy (2016a;2016b), for example, analyzed pitches from the Dragon's Den while Moreau (2018) explored pitches from its American counterpart, Shark Tank.…”
Section: Identifying Focuses Definitions and Purposes Of Pitchmentioning
confidence: 99%
“…The revision revealed that researchers (Denning & Dew, 2012;McCollough, Devezer & Tanner, 2016;Daly & Davy, 2016a) usually claim that a considerable part of the definitions of pitch come from nonacademic sources, mainly, written press, websites, and TV Shows. Based on the literature review, Table 1 presents classes of pitch and their definitions.…”
Section: Identifying Focuses Definitions and Purposes Of Pitchmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, sales pitches have been analysed in terms of rhetorical strategies (e.g. Clark, 2008; Daly and Davy, 2016a, 2016b). However, despite acknowledging the mutation that has occurred in public speaking practice in recent years (Crowe and Frank, 2016; Frobish, 2000), there is little systematic – and critical – appraisal of these new digital formats linked to the hypothesis that they be part of a similar social phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…En un trabajo complementario del que aquí introducimos, hemos dado cuenta de la manera en que la imagen propia que presenta el sujeto que pretende persuadir, así como el empleo que hace de determinados signos paralingüísticos, funciona, estraté-gicamente, apelando a la emoción, aunque también se utilizan para captar la atención y resaltar contenido relevante y para estructurar la actividad comunicativa (Cestero, en prensa). Atendemos ahora al empleo que hacen sujetos emprendedores de negocios de los signos quinésicos en discursos públicos de presentación de empresas o productos, que, hasta ahora, no ha sido tratado con detenimiento, ni analizado en profundidad (Daly y Davy, 2016), y detallamos cómo, con ellos, se capta la atención y se resalta información, se estructura la actividad comunicativa, se aporta contenido semántico y, además o a la vez, se muestran emociones, actitudes y estados.…”
Section: Introducción: Comunicación No Verbal En Persuasiónunclassified